2016
DOI: 10.1177/0266666915587129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an electronic performance support system for crime scene investigation units in Turkey

Abstract: The primary goal of this study was to present the summative evaluation findings of an initial implementation to investigate the impact, effectiveness and perceived benefits of the Electronic Performance Support System (EPSS) on the performance of Crime Scene Investigation (CSI) officers in Turkey. A sequential explanatory strategy as a procedure of mixed method design was used to collect data through a survey, interviews, and computer logs. While 191 CSI officers participated in the quantitative part of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…One of the most frequently mentioned benefits of EPSS is its potential to support employee performance (Barker and Banerji, 1995;Gery, 1995;Chang, 2004;Nguyen and Klein, 2008) and as a result different aspects of employee productivity (Bastiaens, 1999;Altalib, 2002). Several empirical studies have reported positive effects of EPSS on various measures of performance (Bastiaens, 1999;van Schaik et al, 2002;Mao and Brown, 2005;Nguyen et al, 2005;Gal and Nachmias, 2011;Lanese and Nguyen, 2012;Rios et al, 2013;Nuss et al, 2014;Yakin and Yildirim, 2016;Gal et al, 2017;Ugur-Erdogmus and Cagiltay, 2019). These were, for instance, positive effects on expertise reports or speed of task completion of police officers in Turkey (Yakin and Yildirim, 2016) and positive effects on time used for and quality of maintenance procedures of the engine air bleed system on a Boeing 737 aircraft (Rios et al, 2013).…”
Section: Electronic Performance Support Systems and Informal Workplac...mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most frequently mentioned benefits of EPSS is its potential to support employee performance (Barker and Banerji, 1995;Gery, 1995;Chang, 2004;Nguyen and Klein, 2008) and as a result different aspects of employee productivity (Bastiaens, 1999;Altalib, 2002). Several empirical studies have reported positive effects of EPSS on various measures of performance (Bastiaens, 1999;van Schaik et al, 2002;Mao and Brown, 2005;Nguyen et al, 2005;Gal and Nachmias, 2011;Lanese and Nguyen, 2012;Rios et al, 2013;Nuss et al, 2014;Yakin and Yildirim, 2016;Gal et al, 2017;Ugur-Erdogmus and Cagiltay, 2019). These were, for instance, positive effects on expertise reports or speed of task completion of police officers in Turkey (Yakin and Yildirim, 2016) and positive effects on time used for and quality of maintenance procedures of the engine air bleed system on a Boeing 737 aircraft (Rios et al, 2013).…”
Section: Electronic Performance Support Systems and Informal Workplac...mentioning
confidence: 99%
“…Several empirical studies have reported positive effects of EPSS on various measures of performance (Bastiaens, 1999;van Schaik et al, 2002;Mao and Brown, 2005;Nguyen et al, 2005;Gal and Nachmias, 2011;Lanese and Nguyen, 2012;Rios et al, 2013;Nuss et al, 2014;Yakin and Yildirim, 2016;Gal et al, 2017;Ugur-Erdogmus and Cagiltay, 2019). These were, for instance, positive effects on expertise reports or speed of task completion of police officers in Turkey (Yakin and Yildirim, 2016) and positive effects on time used for and quality of maintenance procedures of the engine air bleed system on a Boeing 737 aircraft (Rios et al, 2013). Some studies compared the effect of EPSS with traditional training and found EPSS to be at least partly superior (Bastiaens et al, 1995;Mao and Brown, 2005;Gal et al, 2017).…”
Section: Electronic Performance Support Systems and Informal Workplac...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the opinion of IT system users and managers, there is an urgent need to support work efficiency in positions equipped with a computer by providing knowledge necessary to the performed tasks (Lorenowicz et el., 2015). Knowledge should be (see Yakin & Yildirim, 2016):…”
Section: Demand For the Position Trainingsmentioning
confidence: 99%